(untitled) (Revista Internacional de Formação de Professores, 2019)
Initial teacher education is a privileged place to educate qualified professionals. Therefore, it is important to study its curricula. Using a multiple case study methodology, we characterized and compared the initial teacher education curricula of two higher education institutions (University of Lisbon, Portugal, and Malmö University, Sweden) regarding their structure and emphasis given to praxis (internship). We concluded that these teacher education programmes are a result of the implementation of the Bologna process. Their structures are quite different in both institutions and there are differences regarding the duration and distribution of praxis. The importance to know not only the European realities, but also the luso-brazilian realities led us to consider possible future cooperation between Portuguese and Brazilian institutions to broaden this kind of studies.